Video-based decision support for referees in sports games - Schütz, L.-M.; Plessner, H. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
This chapter introduces the use of video-based decision aids in sports games, often referred to as video refereeing. Video referees are not only used in soccer, but in many other sports such as handball and volleyball. In the National Football League, the video referee was already used in 1985. The use of video-based decision-making aids has also been studied scientifically. Overall, it can be seen that the use of video referees makes sports fairer. However, there are also difficulties arising from the use: a foul scene viewed in slow motion is penalized more severely than the same scene viewed in real time.